GEOMETRICALLY FLEXIBLE AND EFFICIENT NUMERICAL SOLUTION TECHNIQUE FOR BRAGG EDGE NEUTRON TRANSMISSION STRAIN TOMOGRAPHY - AGGARWAL, RIYA (Bulletin of the Australian Mathematical Society, 2021)
[...]of the backscattering, the Bragg-edges do not add the scattering angle to the d-spacing error, making this technique an essential alternative for neutron applications requiring a high-resolution d distance, such as strain measurements. Besides that, a strain is a tensor of the second order, while density is a scalar quantity, which makes strain tomography considerably more complicated. [...]numerical methods such as finite element and meshless methods are able to achieve high-resolution strain reconstruction.